Liberty brought us here : the true story of American slaves who migrated to Liberia - Lindsey, Susan E., 1952- (The University Press of Kentucky, 2020)
Between 1820 and 1913, thousands of black people left the United States to start new lives in Liberia, Africa, in what was at the time the largest out-migration in US history. When Tolbert Major, a Kentucky slave and single father, was offered his own chance for freedom, he accepted. He, several family members, and almost seventy other people boarded the Luna on July 5, 1836. After they arrived in Liberia, Tolbert penned a letter to his former owner, Ben Major: "Dear Sir, We have all landed on the shores of Africa and got into our houses. ... None of us have been taken with the fever yet." Drawing on extensive research and fifteen years' worth of surviving letters, the author illuminates the trials and triumphs of building a new life in Liberia, where settlers were free, but struggled to acclimate in an unfamiliar land, coexist with indigenous groups, and overcome disease and other dangers. This book explores the motives and attitudes of colonization supporters and those who lived in the colony, offering perspectives beyond the standard narrative that colonization was solely about racism or forced exile. --